Juridical Analysis of the Role of Investigators in the Crime of Theft with Violence - Abdul Hamid (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
The purpose of this research is to determine investigators' efforts to uncover criminal acts of violent theft and to find out the factors behind someone committing a criminal act of violent theft. Research method with a qualitative analysis approach in obtaining valid, empirically juridical data through interviews, documentation studies, and field observations. Data collection techniques in the form of in-depth interviews with all those involved in matters involving law enforcement officers, law enforcers, and suspects by the research focus, field observations observing events in the research environment, and studying documentation in the form of archives and notes of relevant judges. Conclusion Investigation is an investigative activity with restrictions that involve coercive measures after there is sufficient evidence to make clear a case that is suspected of being a criminal act. Investigation functions to look for incidents that commit crimes based on data and information. Factors that cause someone to commit a crime, so it is easy to find shortcuts by committing crimes that are influenced by environmental and social factors. Economic factors, educational factors, and religious factors are carried out by teenagers because their needs are not met, and there is a lack of parental supervision.